2012
DOI: 10.1038/jhh.2012.29
|View full text |Cite
|
Sign up to set email alerts
|

High-circulating leptin levels are associated with increased blood pressure in uncontrolled resistant hypertension

Abstract: Leptin and aldosterone have been associated with the pathophysiological mechanisms of hypertension. However, despite studies showing the association of leptin with intima-media thickness, arterial distensibility and sympathetic nerve activation, the relationship between leptin and blood pressure (BP) in resistant hypertension (RHTN) is unknown. We aimed to assess the correlation of plasma leptin and aldosterone levels with BP in uncontrolled controlled RHTN (UCRHTN) and CRHTN patients. Plasma leptin and aldost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 37 publications
1
24
1
3
Order By: Relevance
“…Even though some controversies have been found in the literature, imbalanced adipokines levels have been related to hypertension [11][12][13], as well as in vascular manifestations [3,7,14]. Even though some controversies have been found in the literature, imbalanced adipokines levels have been related to hypertension [11][12][13], as well as in vascular manifestations [3,7,14].…”
Section: Adipokines Arterial Stiffness and Resistant Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though some controversies have been found in the literature, imbalanced adipokines levels have been related to hypertension [11][12][13], as well as in vascular manifestations [3,7,14]. Even though some controversies have been found in the literature, imbalanced adipokines levels have been related to hypertension [11][12][13], as well as in vascular manifestations [3,7,14].…”
Section: Adipokines Arterial Stiffness and Resistant Hypertensionmentioning
confidence: 99%
“…Also, arterial stiffness is a frequent vascular complication in hypertensive patients and represents an increased cardiovascular risk [10]. Imbalanced levels of adipokines have been associated with hypertension and BP control [11][12][13], as well as vascular manifestations of the condition [3,7,14]. In this review, we summarize the findings on the implications of the most studied adipokines: adiponectin, leptin and resistin, in arterial stiffness and hypertension.…”
mentioning
confidence: 99%
“…Several investigators have reported the existence of as-yet-unidentified macromolecular stimuli of aldosterone synthesis released from cultured human adipocytes, [10][11][12] whereas a positive correlation between aldosterone and the adipocyte-derived hormone leptin has recently been established. 13 Based on these data, we hypothesized that the adipocyte-derived hormone leptin directly regulates aldosterone synthase (CYP11B2) expression and aldosterone production in adrenal zona glomerulosa cells and promotes cardiovascular dysfunction via aldosterone-dependent mechanisms.…”
mentioning
confidence: 99%
“…Plasma leptin has shown a positive relationship with blood pressure by simple correlation in previous reports. However, in multiple regression models, the relationship has shown contradictory results [16–19]. Aging and fat mass affect both plasma leptin and blood pressure; however, the importance of the relationship is thought to diminish after adjusting for covariates [18].…”
Section: Discussionmentioning
confidence: 99%
“…A high plasma leptin concentration is also known to elevate the blood pressure [16–19]. However, older adults with frailty who were considered to have high plasma leptin levels were also reported to have low blood pressure and high mortality [20–23].…”
mentioning
confidence: 99%